FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN PETANI DALAM PENGAMBILAN KREDIT DI BRI UNIT DESA KECAMATAN POLOKARTO KABUPATEN SUKOHARJO - Parmiyatun Parmiyatun; Totok Mardikanto; Suminah Suminah (AGRITEXTS: Journal of Agricultural Extension, 2006)
For meeting the farmer's capital needs, the government expands credit network through Village Unit BRJ· and Village Unit Cooperative (KUD). The objectives of this research are to find out the farmer's decision making in taking up credit in Village Unit BR!, to find out some factors affecting the farmer's · decision making in taking up credit in Village Unit BR!, to find out how far the significant relation between factors affecting the farmer's decision making and farmer's decision in taking up credit in Village Unit BR! in Sub district Polokarto.The result of research shows that factors affecting the farmer's decision making deriving from the farmers in age factor is included in median score of 3, namely more than 40 years to 50 years, formal education factor included in median score of 2, namely elementary school graduated, economical capability included in median score of 4, namely saving occasionally, crop factors included in median score of 3, namely between 100% up to 125%. For the factors deriving from the bank side, the credit procedure factor is included in median score of 5 namely very easy, official service factor included in median score of 4, namely 5 to J 0 minutes, the credit size factor included in median score of 2, namely between 1 to 15 millions, interest rate factor is in median score of 1, namely more than 2, 5%, loan duration factor is in median score of 4, namely on time, realization factor is in median score of 4, namely between 1 to 2 weeks, return factor is in median score of 3, namely more than J planting season to 2 planting seasons, sanction factor is in median score of 2, namely more than 2% to 2, 5%, product price factors is in median score of 3, namely stable, customer's experience factor of other farmer is in median score of 4, namely rather favorable. While the farmer's decision in taking up credit in Village Unit BR/ is included high.